Cities as partners: the case of Kampala - Saliba, S; Silver, I (Refugee Studies Centre, University of Oxford, 2020)
The arrival of large numbers of refugees in western European cities since 2015 has spurred widespread endorsement of the role of these city governments in addressing displacement. Displacement to cities in other countries worldwide, however, also demands attention.